2015
DOI: 10.1111/wbm.12085
|View full text |Cite
|
Sign up to set email alerts
|

Can light intensity influence the tolerance of Synedrellopsis grisebachii to glyphosate?

Abstract: Plant susceptibility to herbicides is related to several factors, including the environmental conditions under which the plants develop. Two experiments were carried out using Synedrellopsis grisebachii plants in two different developmental stages (vegetative and reproductive), with the goal of studying plant susceptibility to the herbicide, glyphosate, and the dependence of this susceptibility on light intensity (full sunlight and 70% shading), correlated with leaf anatomy. The experimental design for both ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This differences could be addressed to the use of different glyphosate formulations and dose rate, the application technique (manual or mechanical) employed by farmers, and the agro environment conditions (Neve et al, 2014; Renton et al, 2014; Jussaume and Ervin, 2016; Matzrafi et al, 2016; Owen, 2016). It has been shown that an increase in the relative humidity and temperature increases the glyphosate absorption, translocation, and toxicity in many weed species (Ge et al, 2011; Hatterman-Valenti et al, 2011; Vila-Aiub et al, 2012; Santos et al, 2016). This research also revealed that the low GR 50 and LD 50 values for the susceptible accessions showed that glyphosate has been a very effective tool for farmer for over 15 years, as has been shown in P. hysterophorus from Colombia, Dominican Republic, and Florida (Fernandez, 2013; Rosario et al, 2013; Jimenez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This differences could be addressed to the use of different glyphosate formulations and dose rate, the application technique (manual or mechanical) employed by farmers, and the agro environment conditions (Neve et al, 2014; Renton et al, 2014; Jussaume and Ervin, 2016; Matzrafi et al, 2016; Owen, 2016). It has been shown that an increase in the relative humidity and temperature increases the glyphosate absorption, translocation, and toxicity in many weed species (Ge et al, 2011; Hatterman-Valenti et al, 2011; Vila-Aiub et al, 2012; Santos et al, 2016). This research also revealed that the low GR 50 and LD 50 values for the susceptible accessions showed that glyphosate has been a very effective tool for farmer for over 15 years, as has been shown in P. hysterophorus from Colombia, Dominican Republic, and Florida (Fernandez, 2013; Rosario et al, 2013; Jimenez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Sherner et al (2017) reported greater glyphosate efficacy on flooded soils, Tworkoski et al (1998) described greater efficacy under dry soil conditions, and Zanatta et al (2007) found no difference between varying soil moisture levels. The effect of elevated irradiance levels has been shown to increase (Coupland 1983; Kells and Rieck 1979), decrease (Santos et al 2016; Sharkhuu et al 2014), or be unrelated to glyphosate performance (Adkins et al 1998b; Masiunas and Weller 1988).…”
Section: Introductionmentioning
confidence: 99%
“…(Bressanin et al, 2014) and tolerant weeds, such as the tropical spiderwort -Commelina benghalensis L., coatbuttons -Tridax procumbens L., and Cinderella weed -Synedrellopsis grisebachii Hieron. & Kuntze (Santos et al, 2016), which normally infest orange groves (Pinotti et al, 2009). On the other hand, there are several cover crop species with allelopathic potential that can contribute to weed control (Linares et al, 2008).…”
Section: Introductionmentioning
confidence: 99%